Efficient Ab-Initio Electron Transport Calculations for Heterostructures by the Nonequilibrium Green's Function Method. (27th October 2014) - Takaki, Hirokazu; Kobayashi, Nobuhiko; Hirose, Kenji
Abstract : We present an efficient computation technique for ab-initio electron transport calculations based on density functional theory and the nonequilibrium Green's function formalism for application to heterostructures with two-dimensional (2D) interfaces. The computational load for constructing the Green's functions, which depends not only on the energy but also on the 2D Bloch wave vector along the interfaces and is thus catastrophically heavy, is circumvented by parallel computational techniques with the message passing interface, which divides the calculations of the Green's functions with respect to energy and wave vectors. To demonstrate the computational efficiency of the present code, we perform ab-initio electron transport calculations of Al(100)-Si(100)-Al(100) heterostructures, one of the most typical metal-semiconductor-metal systems, and show their transmission spectra, density of states (DOSs), and dependence on the thickness of the Si layers.